The Effectiveness of Digital Marketing in Increasing Tourist Visits to Gunung Dago Nature Tourism Parung Panjang, Bogor, West Jawa - Simamora, Vera; Hendarti, Fariza; Octavianisa, Rizqia (Yayasan Ilomata, 2025)
Gunung Dago Nature Tourism, located in Parung Panjang District, Bogor Regency, West Java, is a nature-based tourist destination officially opened on January 1, 2019. As a tourism attraction requiring a sustainable promotional strategy, the management has implemented digital marketing through various social media platforms. However, despite utilizing online media for branding and promotion, the number of tourist visits has not increased significantly and has even declined. This contradicts previous research findings, which suggest that optimizing digital marketing in tourism promotion can significantly increase visitor numbers. This study aims to analyze the effectiveness of digital marketing as a promotional strategy for Gunung Dago tourism. The research employs a qualitative approach with a case study method. Data were collected through observations, interviews, and documentation, with informants selected using purposive sampling techniques. The data were analyzed using a descriptive qualitative approach. The findings indicate that digital marketing is carried out through social media platforms such as Instagram, Facebook, TikTok, and YouTube. Additionally, an official website is available; however, its management falls under the authority of the Bogor Regency Government, resulting in suboptimal utilization. The implementation of digital marketing in Gunung Dago still faces challenges, primarily due to the management's heavy reliance on Instagram as the primary promotional medium, while the website remains underutilized. The main obstacles identified include limited human resource capabilities in managing various digital platforms. Therefore, technology-based training for tourism managers and the provision of supporting infrastructure are necessary to enhance the effectiveness of digital marketing strategies.